Low-dose Indonesian Aloe vera Increases Viability and Migration of the Fibroblast: An In Vitro Study - Rizqi, Januar; Fitriawan, Akbar Satria (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Important stages in wound healing involve homeostasis, inflammation, proliferation, and remodeling phases. Fibroblasts are essential factors in the healing pathway through the process of cell proliferation and migration. Aloe vera contains various active compounds used for anti-inflammatory, antimicrobial, immunomodulatory, anticancer, and wound healing. AIM: This study aimed to evaluate the effect of A. vera on the viability and migration of fibroblast cells. MATERIALS AND METHODS: Fibroblasts were cultured in a monolayer with Dulbecco’s Modified Eagle Medium containing 10% fetal bovine serum, 1% pinstripe, and 0.5% fungizone. We use fresh A. vera leaves extracted with 95% ethanol. Cell viability will be evaluated using the MTT test and microscopic evaluation. Cell migration was tested using an in vitro wound scratch assay and analyzed with ImageJ software. RESULTS: A. vera stimulated cell viability compared to control (p < 0.05). Administration of A. vera does not change shape and is not toxic to fibroblasts. A. vera stimulated cell migration at doses of 250, 125, 50, and 5 μg/mL compared to control after 24 h of intervention. At 48 h incubation, migration doses of 250, 50, and 5 μg/mL were higher than control (p < 0.05). CONCLUSIONS: A. vera extract may effectively wound healing by increasing viability and migration of fibroblast cells.